1984
DOI: 10.3181/00379727-177-41969
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene Uptake by Serum Lipids: Correlation with Triglyceride Concentration

Abstract: An in vitro study of the relationship between benzo[a]pyrene (BaP) association with serum lipoproteins (LP) and LP composition was conducted using human subjects. BaP partitioning into different serum LP ranged from 53 to 71% of available BaP. Efficiency of BaP partitioning was examined for the relationship with lipid components of different sera. The data indicate that triglyceride (TG) concentrations were more directly correlated with BaP uptake than were concentrations of other LP components. Adjusting sera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the case of TCDD, its distribution into adipose tissue is greater at low exposure levels 29. Obese persons tend to have higher lipid levels in circulation, and in the case of lipophilic chemicals whose blood concentrations are dependent on blood lipid levels, whole blood chemical quantities may appear higher in obese persons than lean persons even if total body burdens are equivalent 32,33. In other words, the dilution effect of higher body mass may be masked by higher blood lipids when sampling serum or whole blood to assess lipophilic chemical exposure.…”
Section: Unique Susceptibility Of Obese Children and Adolescentsmentioning
confidence: 99%
“…In the case of TCDD, its distribution into adipose tissue is greater at low exposure levels 29. Obese persons tend to have higher lipid levels in circulation, and in the case of lipophilic chemicals whose blood concentrations are dependent on blood lipid levels, whole blood chemical quantities may appear higher in obese persons than lean persons even if total body burdens are equivalent 32,33. In other words, the dilution effect of higher body mass may be masked by higher blood lipids when sampling serum or whole blood to assess lipophilic chemical exposure.…”
Section: Unique Susceptibility Of Obese Children and Adolescentsmentioning
confidence: 99%
“…Lymphoid organs and cells of the immune system are strategically located to monitor physiological portals of entry and may be among the first cells to participate in the absorption, distribution and biotransformation of xenobiotic compounds entering an animal. In mammals, ingested fat-soluble chemicals are taken up into the lacteal absorption from the gut and transit the mesenteric lymphatic drainage to the vascular circulation via the thoracic duct, bypassing the liver (Yoo et al, 1984;Busbee et ai, 1985;Wilson el al., 1985). Therefore, fat soluble chemicals in the diet incorporated into chylomicrons are peripherally distributed prior to encountering hepatic detoxification mechanisms, with potential exposure of essentially all peripheral organs and cells to unmetabolised fat-soluble hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data indicate that triglyceride concentrations are more directly correlated with B[a]P uptake than are concentrations of other lipoproteins, and suggest that a small change in serum triglyceride concentration could cause a significant change in the uptake of B[a]P, thereby influencing the level of circulating carcinogen [Yoo et al, 1984]. In this study, simple regression analysis showed a significant inverse relationship between triglyceride concentrations and DNA-adduct levels in the aorta of the ApoE*3-Leiden mice.…”
Section: Discussionmentioning
confidence: 99%